2021
DOI: 10.1590/1678-4499.20200489
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent selection for high iron and zinc concentrations in black bean grain

Abstract: The iron concentration (FeC) and zinc concentration (ZnC) in common bean grain are quantitative traits, and appropriate breeding techniques are required to achieve genetic gain. The aim of this study was to obtain a recurrent selection population of black bean to increase the FeC and ZnC in the grain and to select the superior progenies for formation of the next cycle and obtain lines. The base population was formed by crosses among ten parents. A total of 351 progenies were obtained, and, after two generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 33 publications
(29 reference statements)
1
9
0
Order By: Relevance
“…There was a significant effect of environments for all the traits evaluated (Table 1), indicating that the different locations, years, and crop seasons substantially alter the response of the genotypes. Several studies have reported the effect of environment on the expression of agronomic and nutritional traits in common bean (Dias et al., 2021; Martins et al., 2016; Queiroz et al., 2021). There was also a significant difference among the genotypes for all the traits, except for plant architecture, according to analysis of deviance (Table 1), which shows the genetic variability among the lines and/or cultivars evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There was a significant effect of environments for all the traits evaluated (Table 1), indicating that the different locations, years, and crop seasons substantially alter the response of the genotypes. Several studies have reported the effect of environment on the expression of agronomic and nutritional traits in common bean (Dias et al., 2021; Martins et al., 2016; Queiroz et al., 2021). There was also a significant difference among the genotypes for all the traits, except for plant architecture, according to analysis of deviance (Table 1), which shows the genetic variability among the lines and/or cultivars evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…There was also a significant difference among the genotypes for all the traits, except for plant architecture, according to analysis of deviance (Table 1), which shows the genetic variability among the lines and/or cultivars evaluated. Significant difference among genotypes is essential for there to be progress from selection, and several studies have reported high genetic variability for the nutritional traits (Caproni et al., 2020; Di Prado et al., 2019; Martins et al., 2016; Pereira et al., 2014; Queiroz et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations